PRIMARY CELL CULTURE OF AEDES ALBOPICTUS MIDGUT CELLS: A PROSPECTIVE MODEL FOR IN VITRO STUDY OF ARBOVIRUSES - Roy, Enakshi; Sinha, Moonmoon; Katoch, Shailja; Chakraborty, Urmita; Das, Satadal; Sarkar, Debabrata; Nayak, Debadatta; Khurana, Anil; Manchanda, Raj Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Midgut cells play a key role in the propagation of mosquito borne Arboviruses. The existing mosquito cell lines for studying viral pathogenesis are derived either from larvae or from eggs since there is no cell line available from the mosquito midgut. Therefore, to delineate the in situ viral interaction which naturally occurs within the mosquito midgut and represent cellular pathogenesis in human beings, the present work was aimed to develop a primary cell line from the midgut cells of Aedes albopictus. Methods: The midgut cells of A. albopictus were collected, cultured and incubated at 28Â°C to study the growth after every 24 hrs for 7 days. Result: The primary cell culture showed an increasing growth pattern of columnar cells up to 48 hrs followed by decrease in cell population afterward. However, the number of stem cells increased significantly throughout the study period, and their population outnumbered the columnar cells after 72 hrs. There was no significant change of goblet cells and regenerating cells which were scanty in number throughout the experiment. Conclusion: The present method will help to develop the individual cell lines from mosquito midgut and study the host pathogen interaction in arboviral diseases in future.